Social vulnerabilities among immigrants and refugees in emergencies and disasters: a systematic review - Doust Mohammadi, Mohammad Mahdi; Salmani, Ibrahim; Farahmandnia, Hojjat (Frontiers in Public Health, 2024)
Background Due to cultural, economic, and societal factors, immigrants and refugees are pivotal groups in dealing with social vulnerability in disasters. Ignoring or inadequate attention to those groups in preparing for and responding to disasters and health emergencies could decrease the effectiveness of efforts. This article aims to identify the most basic social vulnerabilities among immigrants and refugees and provide effective solutions to alleviate or eliminate these vulnerabilities. Methods This systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The main keywords include Social Vulnerabilities, Immigrants, Refugees, and Disasters. All articles published up to February 2023 were reviewed regardless of language and location. A total of 575 articles were extracted from SCOPUS, Web of Science, ScienceDirect, ProQuest, PubMed, EMBASE, and PsycINFO databases, and finally, 14 articles were selected for full-text analysis. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) was used to evaluate the quality of the selected articles. Results Fourteen articles including 4 qualitative and 10 quantitative articles were selected and analyzed in this review. The findings showed: 1. According to the consensus of the studies, the most vulnerable people who need urgent care during an epidemic due to their special conditions are immigrants and refugees; 2. In most countries, no database provides reliable, up-to-date, and accurate statistics about these people; 3. Refugees usually hesitate to express their vulnerability and receive services due to the fear of deportation; and 4. The main challenges faced by refugees are socio-economic problems such as language problems, lack of emotional and social support, and living in crowded places. Conclusion Considering the prevalence of migration among countries, it is essential to identify the social problems and vulnerabilities of immigrants and provide effective solutions to cope with their challenges, especially during crises and emergencies. Systematic review registration https://clinicaltrials.gov/, identifier CRD42022371345.